Recreating the OSIRIS-REx slingshot manoeuvre from a network of ground-based sensors. (27th November 2020) - Jansen-Sturgeon, Trent; Hartig, Benjamin A. D.; Madsen, Gregory J.; Bland, Philip A.; Sansom, Eleanor K.; Devillepoix, Hadrien A. R.; Howie, Robert M.; Cupák, Martin; Towner, Martin C.; Cox, Morgan A.; Nevill, Nicole D.; Hoskins, Zacchary N. P.; et al.
Abstract: Optical tracking systems typically trade off between astrometric precision and field of view. In this work, we showcase a networked approach to optical tracking using very wide field-of-view imagers that have relatively low astrometric precision on the scheduled OSIRIS-REx slingshot manoeuvre around Earth on 22 Sep 2017. As part of a trajectory designed to get OSIRIS-REx to NEO 101955 Bennu, this flyby event was viewed from 13 remote sensors spread across Australia and New Zealand to promote triangulatable observations. Each observatory in this portable network was constructed to be as lightweight and portable as possible, with hardware based off the successful design of the Desert Fireball Network. Over a 4-h collection window, we gathered 15 439 images of the night sky in the predicted direction of the OSIRIS-REx spacecraft. Using a specially developed streak detection and orbit determination data pipeline, we detected 2 090 line-of-sight observations. Our fitted orbit was determined to be within about 10 km of orbital telemetry along the observed 109 262 km length of OSIRIS-REx trajectory, and thus demonstrating the impressive capability of a networked approach to Space Surveillance and Tracking.